Pengaruh Work Family Conflict terhadap Komitmen Organisasi pada Dosen Universitas Swasta X di Jakarta - Amalia Ikhsani Wijayaputri; Anna Rozana (UNISBA Press, 2023)
Abstract. Lecturers who are married perform a dual responsibility, that of parents who are responsible for raising their children., then as a lecturer who is obligated to abide with the agency's standards. Organizational commitment goes beyond just lecturers' participation in the organization; it also involves maintaining one's presence within the organization and taking part in the pursuit of its objectives. There is a conflict between the demands of the lecturer's job and the expectations of the lecturer's role in the family, resulting in Work Family Conflict. The purpose of this research is to ascertain the impact of Work Family Conflict on organizational commitment to lecturers, both male and female. This research uses the causality method and is quantitative in nature. The 265 academics who made up the population in this study were all lecturers. The 159 lecturers that were included in the research sample were chosen using Convenience Sampling, a Non Probability Sampling technique. Simple regression is a data analysis approach. The Work Family Conflict Scale, established by Carlson and Kacmar and translated and adapted by Indah Kuntari, is the measurement device used in the Variable Work Family Conflict (2014). The organizational commitment measuring tool makes use of an organizational commitment scale created by Ingarianti that is based on the idea of Mowday, Steers, & Porter (2015). The result of the research is that the lecturers' Work Family Conflict belongs to the high category. The highest dimension is Strain-Based Conflict Family Interference With Work. The level of organizational support for lecturers comes within the low category. Identification is the lowest dimension. The beta value is -0.229, and the significance value is 0.004 < 0.05, implying that the Work Family Conflict data has a negative and substantial impact on organizational commitment to lecturers. Keywords : Work Family Conflict and Organizational Commitment Abstrak. Dosen yang sudah berkeluarga mempunyai peran ganda yaitu sebagai orang tua yang memiliki tugas dan tanggung jawab mengurus anak, lalu sebagai dosen yang harus mengikuti aturan intansi. Komitmen organisasi, tidak hanya sebatas dengan keterlibatan dosen terhadap organisasi, tetapi mempertahankan keberadaannya di dalam organisasi dan turut serta mencapai tujuan organisasi. Adanya konflik yang dirasakan oleh dosen dalam pekerjaan dan tuntutan peran dalam kelurga sehingga dosen mengalami work family conflict. Penelitian ini bertujuan untuk mengetahui pengaruh work family conflict terhadap komitmen organisasi pada dosen baik perempuan maupun laki-laki. Penelitian ini merupakan penelitian kuantitatif dengan menggunakan metode kausalitas. Populasi dalam penelitian ini yaitu seluruh dosen yang berjumlah 265 dosen. Sampel penelitian berjumlah 159 dosen yang diambil dengan menggunakan non probabilitas sampling, yaitu convenience sampling. Teknik analisis data menggunakan regresi sederhana. Alat ukur yang digunakan pada variable work family conflict yaitu menggunakan work family conflict scale yang dikembangkan oleh Carlson, Kacmar yang di adaptasi dan diterjemahkan oleh Indah Kuntari (2014). Alat ukur komitmen organisasi menggunakan skala komitmen organisasi berdasarkan teori Mowday, Steers, & Porter yang dikembangkan oleh Ingarianti (2015). Hasil penelitian adalah Work Family Conflict pada dosen tergolong pada kategori tinggi. Dimensi tertinggi yaitu Strain-based conflcit family interference with work. Komitmen organisasi pada dosen tergolong pada kategori rendah. Dimensi terendah yaitu Identifikasi. Nilai beta sebesar -0,229 dan nilai signifikansi sebesar 0,004 < 0,05 maka dapat disimpulan bahwa data work family conflict berpengaruh negatif dan signifikan terhadap komitmen organisasi pada dosen. Kata Kunci : Work Family Conflict dan Komitmen Organisasi.